2009
DOI: 10.1016/j.geoderma.2008.11.037
|View full text |Cite
|
Sign up to set email alerts
|

Interactions between metals and soil organic matter in various particle size fractions of soil contaminated with waste water

Abstract: . Interactions between metals and soil organic matter in various particle size fractions of soil contaminated with waste water. Geoderma, Elsevier, 2009Elsevier, , vol. 1, pp. 217-223. 10.1016Elsevier, /j.geoderma.2008 Open Archive TOULOUSE Archive Ouverte (OATAO) OATAO is an open access repository that collects the work of Toulouse researchers and makes it freely available over the web where possible. Only scarce field studies concern the consequences of natural soil organic matter (SOM) and metal intera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
71
2
4

Year Published

2011
2011
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 176 publications
(82 citation statements)
references
References 48 publications
(56 reference statements)
5
71
2
4
Order By: Relevance
“…Therefore, the enrichment in light Zn isotopes with an increasing proportion of stable OC likely results from the stabilization of plant-derived Zn-organic compounds, which are usually relatively enriched in light Zn isotopes (Jouvin et al, 2012;Moynier et al, 2009;Weiss et al, 2005;Viers et al, 2007Viers et al, , 2015Couder et al, 2015;Tang et al, 2016;Caldelas and Weiss, 2017), through association with the soil mineral matrix. This interpretation is in line with previous studies that report plant-derived Zn being mainly found in organo-metallic complexes associated with the clay fraction which are relatively resistant to biodegradation (Quenea et al, 2009). …”
Section: Influence Of the Presence Of Stable Organic Carbon On Zn Isosupporting
confidence: 93%
“…Therefore, the enrichment in light Zn isotopes with an increasing proportion of stable OC likely results from the stabilization of plant-derived Zn-organic compounds, which are usually relatively enriched in light Zn isotopes (Jouvin et al, 2012;Moynier et al, 2009;Weiss et al, 2005;Viers et al, 2007Viers et al, , 2015Couder et al, 2015;Tang et al, 2016;Caldelas and Weiss, 2017), through association with the soil mineral matrix. This interpretation is in line with previous studies that report plant-derived Zn being mainly found in organo-metallic complexes associated with the clay fraction which are relatively resistant to biodegradation (Quenea et al, 2009). …”
Section: Influence Of the Presence Of Stable Organic Carbon On Zn Isosupporting
confidence: 93%
“…Colloid has the highest distribution factor of the Cd and Pb. Studies on the relationship among urbanized areas, waste water and mining area soil present the same results, suggesting that Cd and Pb accumulate primarily in fine particles (Luo et al 2011;Harter and Naidu 1995;Quenea et al 2009). Macro-aggregates have the highest mass loading for Cd and Pb, followed by colloid and micro-aggregates, in a study of typical black and bog arable soils (Gong et al 2012).…”
Section: Characteristics Of Heavy Metal and Environmental Effect In Tmentioning
confidence: 72%
“…Acosta et al [11] figured out that the high amounts (60-80%) of calcite and dolomite was the main reason of metals accumulation in fine fractions in the soils of urban parks in Murcia City, Spain. Quenea et al [12] found that Zn seemed to be mainly bounded to soil organic matter associated with clay particles, while Pb seemed to prefer to interact directly with the mineral surfaces versus the organic matter in a soil contaminated by waste water. Tang et al [13] analyzed organic carbon and heavy metals contents for the separated nanocolloidal particles (five fractions from 250 m to <0.1 m) from some mining sites in China and observed a good correlation between Cu, Cd and organic carbon.…”
Section: Introductionmentioning
confidence: 99%